Escherichia coli O157:H7 attachment, survival, growth, and control on stainless steel and in meat brining solutions and its thermal inactivation in non-intact beef - Adler, Jeremy Michael, author; Sofos, John Nikolaos, advisor; Kendall, Patricia A. (Patricia Ann), 1947-, committee member; Nightingale, Kendra K., committee member; Belk, Keith E., committee member (Colorado State University. Libraries, 2010)
The three studies described in this dissertation examined (1) the effects of the initial level of environmental hydration, nutrient density, natural flora, and fluid flow on the strength and attachment of Escherichia coli O157:H7 on stainless steel and the subsequent inactivation of pathogen within a biofilm through sanitizer exposure; (2) E. coli O157:H7 survival in model meat brines containing antimicrobials, natural flora, and meat residues; and (3) the extent of thermal inactivation of the pathogen at different depths of non-intact steaks under-cooked by pan-broiling and roasting to a 60°C geometric center temperature from either the frozen or thawed state. In the first study, E. coli O157:H7, transferred to stainless steel and allowed to dry, exhibited stronger strength of attachment to the surface than pathogen cells that were kept hydrated, indicating that the pathogen's optimal physical removal would occur before the surface dried. Once on stainless steel, E. coli O157:H7 cells remained viable and were able to proliferate in a reduced nutrient substrate; however, when competing flora from beef were present, growth was limited and the pathogen demonstrated an increased strength of attachment. Given this, the inactivation of the pathogen within a biofilm through the use of sanitizers was studied. Peroxyacetic acid/octanoic acid, a quaternary ammonium compound, and sodium hypochlorite based sanitizers were effective in inactivating greater than 99.99% (4 log CFU/cm2) E. coli O157:H7 cells in biofilms with and without competing flora by 10 min of exposure; however, peroxyacetic acid/octanoic acid mixture was the most effective as it gave similar reductions after 1 min of exposure. In the second study, the brining ingredients salt and phosphate in combination were sufficient to inhibit E. coli O157:H7 and natural flora growth for up to 48 h in meat brining solutions at 4 and 15°C with and without meat residues; however, both the pathogen and natural flora remained viable with the potential to spread contamination through recirculated brine solutions. Consequently, antimicrobials were studied for the inactivation of the pathogen in the brine solutions. Cetylpyridinium chloride and sodium metasilicate caused immediate and sustained cell reductions to below the detection limit (1.3 log CFU/ml) and were thus identified as to best reduce the probability of product cross-contamination through pathogen transfer in contaminated re-circulated brine injection. In the third and final study, the 5-day storage of non-intact steaks either at 4 or -20°C did not alter their initial contamination level. Pathogen populations were similar in non-intact steaks in the frozen state or allowed to thaw at 4 or 25°C to simulate thawing in the refrigerator or on the kitchen countertop, respectively, suggesting that the microbial safety of non-intact beef was not decreased by the method of thawing as long as steaks were cooked immediately after the desired thawing temperature was reached. Steak size and cooking method affected the thermal inactivation of E. coli O157:H7 as thicker steaks and steaks cooked by pan-broiling had greater pathogen inactivation than thinner and those cooked by roasting, respectively, even though non-intact steaks were cooked to the same internal geometric center temperature of 60°C. These data suggest that steak size and cooking method should be included in lethality guidelines that are designed to ensure the safe preparation of beef products, and when cooking non-intact steaks, pan-broiling is preferred to roasting to ensure their safe consumption. Overall, the results of the studies reported in this dissertation may be useful in the development of cleaning and sanitization programs and improving brining recipes to control E. coli O157:H7 in brining solutions. Further, these data may be useful in developing lethality guidelines for the safe preparation and consumption of non-intact beef products.
Keywords: Escherichia coli O157:H7 -- Growth; sanitizers; meat processing; Escherichia coli O157:H7; cooking; antimicrobials; Foodborne diseases -- Prevention; Beef cattle -- Carcasses -- Contamination; Food -- Safety measures; Meat -- Contamination